Isolation, identification and characterization of soil bacteria for the production of ferulic acid through co-culture fermentation using banana stem waste - Kamaliah, Abdul Samad; Norazwina, Zainol; Hafizuddin, Wan Yussof; Zulsyazwan, Ahmad Khushairi; Nurul Shareena Aqmar, Mohd Sharif; Nur Syahirah, Mohd Syukri (Springer Nature, 2020)
Exploitation of soil bacteria for production of ferulic acid (FA) is extensively performed since bacteria are the largest soil community that have the potential in producing degrading enzymes. This study aims to isolate, identify and characterize the most efficient soil bacteria for high FA yield via co-culture fermentation of banana stem waste (BSW). Bacteria were isolated and screened from acclimatized mixture of soil culture and BSW. ARB programme package and biolog system were employed for identification and characterization. The results reveal that four isolates closely related to Bacillus spp. and one Lysinibacillus sp. had greater potential to produce FA in very large amounts. Specifically, the maximum FA yield of 394.76 mg/kg was achieved using co-culture of Bacillus sp. MB2, Bacillus sp. WB8A and B. pumilus strain WB1A, which was 2.5-fold higher than FA produced by single culture. The profiles of substrate utilization exposed strong hydrolyzation of pectin in those three potential cultures, while one showed strong hydrolyzation of glucuronic acid. The ability to efficiently hydrolyze the components proves that the chosen co-cultures are good sources of hydrolytic enzymes. The results suggest that the co-culture has contributed cooperative actions among the cultures to synergistically breakdown the FA linkage in BSW to produce high FA yield.